A numerical simulation for prediction of infrared radiation emitted from plain surfaces with different geometries - Akbari, Karim; Moayeri, Hamid; Ghassemi, Hassan (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, infrared radiation exiting plain surfaces with different geometries is numerically simulated. Surfaces under consideration are assumed to have steady uniform heat generation inside. Moreover, the boundaries of the surfaces are considered to be at the surroundings temperature. Infrared radiation is calculated based on the temperature profile determined for the surface. The temperature profile of the surface is determined assuming the two dimensional heat conduction equations to govern the problem.
Keywords: numerical simulation; infrared radiation; plain surfaces